Determination of cannabinoids in urine samples by sorbent packed microextraction and gas chromatography-mass spectrometry - Rosendo, Luana May da Silva (2022)
Cannabis is the most consumed illicit drug worldwide, and its legal status is a source of concern. This study proposes a rapid procedure for the simultaneous quantification of ?9- tetrahydrocannabinol (THC), 11-hydroxy-?9-tetrahydrocannabinol (11-OH-THC), 11-nor9-carboxy-?9-tetrahydrocannabinol (THC-COOH), cannabidiol (CBD) and cannabinol (CBN) in urine samples. Microextraction by packed sorbent (MEPS) was used to preconcentrate the analytes, which were detected by gas chromatography-mass spectrometry. The procedure was previously optimized, and the final conditions were: conditioning with 50 µL methanol and 50 µL of water, sample load with two draw-eject cycles, washing with 310 µL of 0.1% formic acid in water with 5% isopropanol; the elution was made with 35 µL of 0.1% ammonium hydroxide in methanol. This fast extraction procedure allowed quantification in the ranges of 1-400 ng/mL for THC and CBD, 5-400 ng/mL for CBN and 11-OH-THC, and 10-400 ng/mL for THC-COOH with coefficients of determination higher than 0.99. The limits of quantification and detection were between 1-10 ng/mL using 0.25 mL of sample. The extraction efficiencies varied between 26 and 85%. This analytical method is the first allowing the determination of cannabinoids in urine sample using MEPS, being a fast, simple and low-cost alternative to conventional techniques.